The Effective Use Of Genre-Based Approach On The Narrative Writing Of Esl Malaysian Secondary School Students - Chong, Voon Sing (2020)
Writing is a skill which reflects one’s language proficiency thus making it the most commonly tested skills to measure one’s language abilities. However, many ESL Malaysian secondary school students still struggle in writing despite many years spent on learning the skill in school. This may be due to the fact that writing is deemed the most challenging task for language learning especially among ESL learners. There are many researches and a proliferation of literature that highlight the challenges faced by these students. It has been demonstrated that this dilemma intervenes with the development of effective writing skills among secondary school students.